Can lower tax rates be bought? Business rent-seeking and tax competition among US States - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2010)
The standard model of strategic tax competition assumes that government policymakers are perfectly benevolent, acting solely to maximize the utility of the representative resident in their jurisdiction. We depart from this assumption by allowing for the possibility that policymakers also may be influenced by the rent-seeking (lobbying) behavior of businesses. This extension to the standard strategic tax competition model implies that business contributions may affect not only the levels of equilibrium tax rates but also the slope of the tax reaction function between jurisdictions, thus enhancing or retarding the mobility of capital across jurisdictions. The model is estimated with panel data for 48 U.S. states and unique data on business campaign contributions. Among other results, we document a significant direct effect of business contributions on tax policy; the economic value of a 1 business campaign contribution in terms of lower state corporate taxes is approximately 6.65.
Keywords: H70; H25; D72; 330; business campaign contributions; state business tax policy; rent-seeking; capital mobility; Steuerwettbewerb; Steuerpolitik; Interessenpolitik; Rent Seeking; Teilstaat; Kapitalmobilität; USA